Determining Candidate Hypobaric Hypoxia Profiles for Humane Killing of Laboratory Mice - Clarkson, Jasmine M.; McKeegan, Dorothy E. F.; Sparrey, Julian; Marchesi, Francesco; Leach, Matthew C.; Martin, Jessica E. (Frontiers in Veterinary Science, 2022)
Millions of mice are used annually in scientific research and must be humanely killed. Despite significant welfare concerns, carbon dioxide exposure remains the most common killing method, primarily because there is no practical and humane alternative. We explored whether hypobaric hypoxia via gradual decompression could induce a non-recovery state in anaesthetised male C57BL/6 and Balb/c laboratory mice. We aimed to determine if this was possible in a feasible time scale with minimal pathological consequences, as a proof-of-principle step. Systematic evaluation of two decompression rates (75ms-1, 150ms-1) and three profile shapes (accelerated, linear, gradual) in a factorial design revealed that hypobaric hypoxia effectively induced a non-recovery state in anaesthetised laboratory mice, irrespective of decompression rate and shape. Mice took longer to reach a non-recovery state with the 75ms-1 decompression rate (75ms-1: 257±8.96s versus 150ms-1: 214±7.26s), with longer latencies in gradual and linear shaped profiles. Accelerated shaped profiles were least susceptible to meaningful refinement via rate. The only pathological changes of concern were moderate middle ear congestion and haemorrhage. These findings suggest that hypobaric hypoxia has potential, and subsequent work will evaluate the welfare consequences of gradual decompression in conscious mice, to identify decompression profiles that minimise welfare harms associated with ear barotrauma.